Evaluating reimbursement of integrated support services using chronic care management (CCM) codes for treatment of hepatitis C among Medicare beneficiaries. Issue 2 (30th August 2019) - Fluegge, Kyle; Bresnahan, Marie P.; Laraque, Fabienne; Litwin, Alain H.; Perumalswami, Ponni V.; Shukla, Shuchin J.; Weiss, Jeffrey J.; Winters, Ann
Abstract: The New York City Department of Health and Mental Hygiene (DOHMH) implemented Project INSPIRE, an integrated model of hepatitis C care coordination and telementoring services, from 2014 to 2017. We evaluated the use of chronic care management (CCM) codes to sustain the intervention. DOHMH data were collected as part of a Healthcare Innovation Award from the Centers for Medicare & Medicaid Services (CMS). A retrospective cohort medical billing study was conducted by assigning INSPIRE activities to procedure codes in both facility and nonfacility settings. Rates for procedures were extracted from the CMS's 2018 fee schedules and added across the eligibility periods for Medicare enrollees. Reimbursement was adjusted on the basis of expected patient attrition and compared to costs. The minimum number needed to treat (NNT) to break even was calculated in each setting. Facility reimbursement was higher than costs, whereas nonfacility reimbursement was lower (both P < .01). The NNT was 23 patients in facilities and 33 patients in nonfacilities; 24 patients per care coordinator were treated annually in INSPIRE. CCM fees alone were insufficient to fully reimburse the costs in either setting. Implementation of an appropriate risk financing strategy is necessary to mitigate financial shortfalls when providing CCM services in facility settings.